1977
DOI: 10.1111/j.1467-1770.1977.tb00126.x
|View full text |Cite
|
Sign up to set email alerts
|

PHONOLOGICAL ENCODING OF CHINESE IDEOGRAPHS IN SHORT‐TERM MEMORY1

Abstract: Three main issues relating to the question of silent speech in reading are addressed: 1) How do Chinese speakers process Chinese ideographs in short‐term memory? 2) How is Chinese students' learning of written English affected by the transition to an alphabetic language? 3) Are the strategies for encoding written words in short‐term memory different for students of diverse language background? Chinese and Spanish bilingual students were tested for short‐term memory encoding strategies on word‐recognition tests… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

1981
1981
2009
2009

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 14 publications
1
8
0
Order By: Relevance
“…This argument was weakened by a recent study with Chinese children who had just started to learn Chinese characters. Chu- Chang and Loritz (1977) found that in a Chinese character recognition task, where a tachistoscopically presented character list was followed by a list consisting of corresponding phonological, visual, and semantic distracting characters. the children responded predominantly to phonological distractors.…”
Section: Phonetic Recoding In Reading Different Orthographiesmentioning
confidence: 99%
“…This argument was weakened by a recent study with Chinese children who had just started to learn Chinese characters. Chu- Chang and Loritz (1977) found that in a Chinese character recognition task, where a tachistoscopically presented character list was followed by a list consisting of corresponding phonological, visual, and semantic distracting characters. the children responded predominantly to phonological distractors.…”
Section: Phonetic Recoding In Reading Different Orthographiesmentioning
confidence: 99%
“…Characters and sentences which were phonemically either similar of dissimilar were presented to fluent native readers of Chinese. Results similar to those of Chu-Chang's (1979) and Chu-Chang and Loritz's (1977) studies were found: subjects required more time to read phonemically similar items.…”
Section: Aural Visualsupporting
confidence: 82%
“…For instance, American children of Harrigan's (1976) and Rozin, Poritsky, and Sotsky's (1971) studies did not know Chinese and learned characters by a visual approach. Chu-Chang and Loritz's (1977) Chinese subjects, who were proficient in Chinese reading but were not skilled in English, made more phonetic errors in Chinese lists and more visual errors in English lists.…”
Section: Aural Visualmentioning
confidence: 96%
See 2 more Smart Citations